2017
DOI: 10.2334/josnusd.16-0856
|View full text |Cite
|
Sign up to set email alerts
|

The oral microbiome and human health

Abstract: Abstract:In this brief review, we discuss our previous research on the relationship between the bacterial composition of salivary microbiota and periodontal disease. Analysis using a terminal restriction fragment length polymorphism method and an international comparison suggest that the predominance of the genera Prevotella and Veillonella in the salivary microbiota is attributable to periodontal disease conditions, and that the predominance of the genus Neisseria indicates healthy periodontal conditions. Fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
173
2
15

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 259 publications
(200 citation statements)
references
References 20 publications
10
173
2
15
Order By: Relevance
“…Furthermore, our finding was inconsistent with a previous cross-sectional study that showed a significant association between salivary microbiome communities and periodontal diseases status [26]. This discrepancy may be explained by differences in study design (prospective cohort study vs. cross-sectional study) and targeted age group (young adults vs. elderly people) [34,35]. The previous studies mentioned that the composition of salivary microbial profiles could be different in relation to age [26,36].…”
Section: Discussioncontrasting
confidence: 97%
See 2 more Smart Citations
“…Furthermore, our finding was inconsistent with a previous cross-sectional study that showed a significant association between salivary microbiome communities and periodontal diseases status [26]. This discrepancy may be explained by differences in study design (prospective cohort study vs. cross-sectional study) and targeted age group (young adults vs. elderly people) [34,35]. The previous studies mentioned that the composition of salivary microbial profiles could be different in relation to age [26,36].…”
Section: Discussioncontrasting
confidence: 97%
“…were significantly higher in the worsening group than in the non-worsening group. Our results partially support those of a previous study [35], which found that Prevotella was associated with periodontal diseases. Other species in our study may indirectly contribute to the worsening of the periodontal health status.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…A positive correlation was found between EBV copy number (qPCR viral data) and bacterial richness (an alpha diversity measure of 16S rRNA observed sequences) which suggests that as the number of bacterial strains increase within a sample, the viral load also increases. In relation to health and disease, high bacterial richness in the saliva has been associated with poor oral health (decayed teeth, periodontitis, and poor oral hygiene) [31,32], and in the vagina, high bacterial diversity has been linked to bacterial In half of the subjects tested, three genera, Catonella, Megasphaera, and Actinobacillus were not present in pre-flight samples, but were detected in samples collected during flight. In those that already had these genera pre-flight, their relative abundances increased in-flight.…”
Section: Viral Reactivationmentioning
confidence: 99%
“…A predominance of Neisseria spp. in the oral cavity indicates healthy conditions of the oral cavity [40,41,42]. Bergeyella spp.…”
Section: Discussionmentioning
confidence: 99%